Comparison of the Incidence of Capsular Formation in Two-Stage, Implant-Based Breast Reconstruction Using an Insertion Funnel and Sizer. (10th July 2021) - Kim, Jun Hyeok; Kim, Jung Hyeou; Lee, Ahwon; Moon, Suk-Ho; Jun, Young-Joon; Oh, Deuk Young
Abstract : Purpose . Capsular formation around breast implants can produce various complications, including erythema, tenderness, discomfort, and breast deformation. Moreover, the capsule is thought to be correlated with breast implant-associated anaplastic large cell lymphoma. The proposed technique of capsule reduction can prevent some of these complications. Thus, the authors suggest a no-touch technique in two-stage, implant-based breast reconstruction. Patients and Methods . This single-center retrospective study evaluated the medical records and digitalized pathological slides of patients who underwent two-stage, implant-based breast reconstruction between February 2018 and May 2019. The selected patients were divided into group A and group B. Group A underwent a no-touch technique that included the following two steps: (1) using a sizer as the frame to create the submuscular and acellular dermal matrix (ADM) pocket for expander insertion and (2) inserting the expander through the funnel. After the second stage of implant insertion, the capsule was harvested for biopsy of the ADM, chest wall, and muscle. Results . This study included 33 breasts (31 patients): 18 in group A and 15 in group B. The capsular thicknesses of the ADM, the chest wall, and the muscle of group A were significantly thinner than those in group B. Pearson's correlation coefficient indicated negative correlations between capsular thickness and age; underlying disease; lesion side; interval of two-stage implant insertion; size of the expander; and radiotherapy, chemotherapy, or hormone therapy. Conclusion . To reduce the incidence of capsular formation following breast reconstruction using prostheses, a no-touch technique that uses a funnel and sizer to avoid implant contact is both efficient and beneficial.